2018
DOI: 10.1108/jes-05-2016-0113
|View full text |Cite
|
Sign up to set email alerts
|

Stimulating broadband adoption: state-owned companies versus tax exemptions – the Brazilian case

Abstract: Purpose The purpose of this paper is to propose a new methodology to assess the economic and social impacts of policies to promote mass access to the internet in fixed broadband. The authors apply the methodology to the Brazilian broadband market. Design/methodology/approach For this purpose, municipal information concerning the provision of EILD is used, and then a stylized model of definition of service penetration based on information regarding the price, the distribution of income and the number of house… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Garcia-Murillo (2005) , focusing on the effect of unbundling policy, found that gross national income (GNI) per capita and the total population of the countries have positive effects on broadband diffusion. Baigorri and Maldonado (2018) , drawing on Brazilian regional data, showed that the price of mobile broadband services is an important factor, and both Na, Hwang, and Kim (2018) and Viard and Economides (2014) indicated that online services which are complementary to broadband connection service are positively correlated with broadband diffusion. Lin and Wu (2013) also identified content as an important factor of broadband adoption.…”
Section: Literature Review On Determinants Of Broadband Adoptionmentioning
confidence: 99%
“…Garcia-Murillo (2005) , focusing on the effect of unbundling policy, found that gross national income (GNI) per capita and the total population of the countries have positive effects on broadband diffusion. Baigorri and Maldonado (2018) , drawing on Brazilian regional data, showed that the price of mobile broadband services is an important factor, and both Na, Hwang, and Kim (2018) and Viard and Economides (2014) indicated that online services which are complementary to broadband connection service are positively correlated with broadband diffusion. Lin and Wu (2013) also identified content as an important factor of broadband adoption.…”
Section: Literature Review On Determinants Of Broadband Adoptionmentioning
confidence: 99%